Makna kontekstual dalam novel If Someday karya sifa mermeida - Nur Khasanah; Misbah Priagung Nursalim (Universitas Ahmad Dahlan, 2020)
Understanding the meaning in communication becomes an important aspect of life. So that the intentions and objectives can be conveyed when communicating. The purpose of this study is to describe the contextual meaning in the novel if someday by Sifa Mermeida. The benefits of this study are (1) as material to add knowledge about the contextual meaning contained in the novel if someday (2) as a reference for further research. This research uses a qualitative method with a descriptive description. Research using reading and note taking techniques. The results of research from the novel if someday that the contextual meaning contained in the contents of the story makes the delivery of intent more interesting. Contextual meaning can be known from the markers in the sentence such as the context of the situation, place, object that refers to the conversation.